Therapeutic Transactions And Informed Concent And Liability Agreement Between Doctors And Patient - Hernayanti Hernayanti; Ratna Ratna; Hari Iskandar; Anindini Winda Amalia; Dewi Atika Putri (Syntax Corporation Indonesia, 2023)
In the therapeutic transaction, the relationship between patient and health service providers tends to bring conflict. Many factors caused that conflict, e.g., lack of patient health understanding, inequality of position between the patient and the provider before the law, and the imperfection of service quality handed over by the Provider. Viewed from a legal standpoint, therapeutic transactions have far-reaching consequences of a reciprocal nature between the patient and the doctor. The execution of informed consent is considered merely a formality to be signed. Juridically, the doctrine of informed consent contains the obligations imposed on doctors and the rights of patients to be fulfilled by doctors. Among the rights of the patient in the doctrine of informed consent are: the right to obtain information about his or her illness and the action to be taken against him; the right to obtain answers to questions he or she asks; the right to choose alternatives; and the right to refuse to initiate action. The right to safety, the right to be informed, the Right to Choice, and the right to Be Heard are also basic consumer rights that doctors must fulfill. These rights are guaranteed by the Consumer Protection Act. The process of informed consent is a manifestation of the preserved equality of relations between doctors and patients who are respectful and communicative; both have rights and duties to be respected, and together they determine the best course of action for patients in order to achieve the desired purpose of medical service. An informed consent is also deemed valid if: (a) the patient has been given explanation or information; (b) the patient or his authorized representative is competent to give a decision or consent; and (c) the consent must be given voluntarily. The process of obtaining informed consent is not running as it should.